2007
DOI: 10.1007/s11064-007-9335-8
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Amyloid Toxicity in Embryonic Rat Astrocytes

Abstract: The senile plaques of Alzheimer's disease contain a high concentration of beta-amyloid (betaA) protein, which may affect the glial population in the septal nucleus, an area of increased risk in AD. BetaA toxicity was measured in septal glia, via a dose-response experiment, by quantifying the effects of three different doses (0.1, 1, and 10 microM) of betaA on cell survival. Astrocytes from embryonic day-16 rats were grown in serum-free media in a single layer culture. Cells were treated on day in vitro (DIV)1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Some of these effects may be indirectly mediated by the glial cells as in another study [3] we have shown that Aβ decreases survival of glial cells at 0.1, 1.0, and 10 µM concentrations under the same circumstances. The glial cell increase in apoptosis due to Aβ was reversed significantly by bFGF and IGF1.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Some of these effects may be indirectly mediated by the glial cells as in another study [3] we have shown that Aβ decreases survival of glial cells at 0.1, 1.0, and 10 µM concentrations under the same circumstances. The glial cell increase in apoptosis due to Aβ was reversed significantly by bFGF and IGF1.…”
Section: Discussionsupporting
confidence: 52%
“…Astrocytes from the cerebral cortex were microdissected and cultured as described previously [3] and plated in 100 mm culture dishes (Corning; Corning, NY). Seven days before neuronal dissection, glial cells were transferred to 12 well cell culture cluster dishes.…”
Section: Dissection and Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that both aggregated Ab protein and the intact cores of Ab plaques isolated from human AD brain tissue, as well as Ab fragments can stimulate astrogliosis, which is also observed in human AD brains (Nagele et al, 2004). Experiments in vitro, have demonstrated that Ab can trigger astroglial Ca 21 signaling, mitochondrial depolarization, and oxidative stress (Abramov et al, 2003(Abramov et al, , 2004; the Ab was also reported to trigger apoptosis in cultured embryonic astrocytes (Assis-Nascimento et al, 2007) and in human AD brains (Kobayashi et al, 2004). Reactive astrocytes were postulated to accumulate large amounts of Ab (Nagele et al, 2003(Nagele et al, , 2004 forming astroglial Ab deposits, although this ability has not been conclusively confirmed.…”
Section: Introductionmentioning
confidence: 99%